Strategi Meningkatkan Pemasaran Pengrajin Tasbih Secara Digital Marketing - Puspita W, Dhevin M.Q Agus; Muawanah, Uliyatul; Uke, Ora Gorez; Aziz, Moh Faisal (Universitas Al-Falah As-Sunniyah Kencong Jember, 2023)
The development of increasingly advanced technology should be an effective marketing, unfortunately the tasbih craftsmen do not understand online marketing, so the marketing of prayer beads only revolves around the local area, this causes no increase in the price of prayer beads. Therefore, we try our best to help tasbih craftsmen by marketing their products online so that the production of prayer beads can be widely known throughout Indonesia and even the world scene. With the widespread introduction of prayer beads, the price of prayer beads will automatically increase and the welfare of the tasbih craftsmen will be more prosperous. In the business world, sales and marketing are very important parts, so that there are many ways that companies take to improve their sales and marketing systems starting from the traditional way. in a modern way. Along with the rapid development of technology, many companies use technology to improve their company's sales and marketing systems. The application of technology, especially the internet in the world of commerce, is a common concern, both the government and the community, the methods used are: 1) Mentoring Method, 2) Steps in Assistance, Results: 1) Community Sharing, 2) Scientific Sharing, The discussion is: 1) Official Discussions, 2) Unofficial Discussions, the dissemination is: 1) HR Partners, 2) Suppliers, 3) Location, 4) Experiments, 5) Product Specifications, 6) Market Segmentation. Therefore we in Krajan hamlet rt: 02 rw: 09 tutul kec balung village, always try to take advantage of the wifi around the tasbih craftsmen community to support digital marketing, this will have an impact on the welfare of the tasbih craftsmen community, income growth when covid 19 becomes It is a good step so that the tasbih craftsman continues to produce prayer beads in an attractive manner to the buyer, besides marketing the prayer beads digitally, marketing is very influential in selling the price of prayer beads in the market.